PEDIATRIC EDUCATION SPECIAL SERIES: A Collaborative Model of Integrated Clinical Education in Physical Therapist Education: Application to the Pediatric Essential Core Competency of Family‐Centered Care. Issue 2 (2017) - Lardinois, Kara L.; Gosselin, Dora; McCarty, Dana; Ollendick, Kathleen; Covington, Kyle
Abstract : Background and Purpose. : Physical therapist (PT) clinical education models in the pediatric setting need to be evaluated. An early, collaborative, integrated clinical education (ICE) model was examined in the pediatric setting to determine the extent to which key characteristics (KCs) and entrustable professional activities (EPAs) of the pediatric essential core competency (ECC) of "family‐centered care for all patient/client and family interactions" are reflected in student self‐evaluation and guided reflection responses. Method/Model Description and Evaluation. : Students' self‐evaluation and guided reflection responses were analyzed using retrospective document analysis. Qualitative coding procedures were used to assess documents for a priori codes including the pediatric ECC of "family‐centered care for all patient/client and family interactions." Outcomes. : In both student self‐evaluation and student guided reflection responses, analysis consistently revealed student discussion of all KCs and most EPAs; the guided reflection responses demonstrated all KCs and nearly all EPAs. Overall, students' assignments revealed a clear emphasis on the KCs of "positivity, " "sensitive, " and "collaborative." The assignments revealed an emphasis on the KC of "responsive, " and the EPAs "factors of the family system that influence the child" and "collaborate with families." Discussion and Conclusion. : The pediatric ECC of "family‐centered care for all patient/client and family interactions" most likely emerged through this early collaborative ICE model due to the model's conceptual framework as well as students having concrete experience in the pediatric setting.